Karakterisasi Baja Chasis Mobil SMK ( Sang Surya ) Sebelum Dan Sesudah Proses Quenching - SETIAWAN, Heri, Pramuko IP.,Ir., MT, Ir. Agus Dwi Anggoro,ST.,M.Eng.,Ph (2015)
The purpose of this study was to determine the percentage of chemical composition, phase constituent microstructure, hardness and impact the price of raw material specimens and heat treatment results in a variation of the component cooling steel plate CHASSIS SMK (the sun) ,. Test material used is low carbon steel plate ST 32 with a test was conducted on the chemical composition test, impact, microstructure and hardness with variation, water quenching, oil quenching. From the test results of chemical composition including carbon steel medium (C = 0.0538%). Results microstructure results obtained in testing the micro structure changes would especially be true in the crystal structure finer on objects that are already experiencing heat treatment. In the photo on the microstructure of low carbon steel plate ST 32 before doing hot especially in the parent metal consisting of ferrite and pearlite grains, this also happens on an already experiencing heat treatment only on objects that have experienced treatment finer crystal structure. Hardness test results obtained price highest average hardness of the specimen quenching oil SAE 20W - 50 of 174 VHN. Results of testing impact toughness price highest average (most clay) is a water quenching specimen of 0.878 J / mm 2.